Stress breeding of neglected tetraploid primitive wheat (Triticum dicoccum, Triticum carthlicum and Triticum polonicum) - Saleh, Maysoun M. (Current Botany, 2020)
Ancient wheats are progressively more considered as valuable resources for genes of interest especially in organic and health food markets which could be introduced into cultivated varieties. Better evaluation of primitive wheats that symbolize a valuable genetic resource may provide breeders with important sources for biotic and abiotic stress tolerance. Emmer wheat (Triticum turgidum subsp. dicoccum) is one of the most ancient of cultivated cereals, makes good bread, higher in fiber than common wheat, emmer is used is for making pasta and bread, with no need at all to use pesticides during growing season, grow in severe environments and minor lands, resistance to Septroria leaf blotch and resistance to Russian wheat aphid and Green bug. Persian wheat (Triticum turgidum ssp. carthlicum) described with many favorable characters, like being a good resistant species to stem rust and powdery mildew, plants have more tillers with good productivity, low temperature tolerant and pre-harvest budding and fairly resistant to fungus diseases. Polish wheat (Triticum turgidum subsp. polonicum) were used for bread making as many forms having grains with high protein content (27%), and it is a great source for high yielding wheat varieties characterized by plump grain, and could be used in genetic bio-fortification of durum wheat and common wheat. Lack of scientific researches and facilities to produce and marketing, in addition to concentrating on new varieties are considered as limitation factors of expanding these species. For better adaptation to climate change and for future food security, it is highly recommended to improve utilization and sustainable use of targeted species and cooperation between scientists and researcher on the national and international levels. This review is an attempt to highlight the value of targeted species with general information about classification, origin and distribution, importance domestication, characterization and conservation, traditional breeding and role of each of molecular biology, tissue culture and mutation in exploiting genetic variation in targeted species.